ECB-Global: Introducing ECB's global macroeconomic model for spillover analysis - Alistair Dieppe; Georgios Georgiadis; Martino Ricci; Ine Van Robays; Björn Van Roye (European Central Bank (ECB), 2017)
In a highly interlinked global economy a key question for policy makers is how foreign shocks and policies transmit to the domestic economy. We develop a semi-structural multi-country model with rich real and financial channels of international shock propagation for the euro area, the US, Japan, the UK, China, oil-exporting economies and the rest of the world: ECB-Global. We illustrate the usefulness of ECB-Global for policy analysis by presenting its predictions regarding the global spillovers from a US monetary policy tightening, a drop in oil prices and a growth slowdown in China. The impulse responses implied by ECB-Global are well in line with those generated by other global models, with international spillovers in ECB-Global generally on the high side given its rich real and financial spillover structure.
Keywords: C51; E30; E50; 330; macro-modelling; multi-country models; spillovers; monetary policy